ChemInform Abstract: Studies on Pyrrolidinones: Chemistry of Dimethoxytriazines. Issue 36 (15th August 2013) - Lucescu, Liliana; Gautret, Philippe; Oudir, Souhila; Rigo, Benoit; Belei, Dalila; Bicu, Elena; Ghinet, Alina
Abstract The synthesis of 3, 5‐dimethoxy‐1, 3, 5‐triazines (III) is developed: demethylation and N‐methylation of these products is studied.